Animal pharm, and more - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Journal of the Caribbean Veterinary Medical Association US$ 25 Euro 27.60 per issue, US$ 40 Euro 44.15 per year